Content validity of the modified barthel index for stroke patients in South Africa - Breytenbach, Fiona (My University, 2016)
Background: The Barthel Index is considered the global golden standard for assessing of one’s performance in self-care tasks, but little research has been performed on the integrity of this outcome measure for the South African stroke population. Aim: The study aimed to determine whether the content validity of the Modified Barthel Index is adequate in assessing the ADL functioning of stroke patients in South Africa. Research design: Mixed methods design using the nominal group technique Methods: Four nominal group technique groups were held consisting of three to six participants per group. The study sample consisted of occupational therapists (n=11) and physiotherapists (n=4) with four or more years working experience (mean=13.7 years) in the field of adult neurorehabilitation in South Africa. Each group was presented with five questions based on the Table of Specifications methodology to analyse the content validity of the Modified Barthel Index. Data analysis followed Van Breda’s steps to analysing multi-group nominal group technique data to establish themes arising from each question and were presented according to final rank scores. Results: The themes receiving the highest rank score for each of the five questions concluded that the Modified Barthel Index should (i) be designed for use by therapists and nurses, (ii) remain in English, (iii) be re-worded to be clear and understandable, (iv) include all aspects of functional mobility, and (v) should accommodate for the effect accessibility barriers have on daily functioning. Conclusion: The Modified Barthel Index requires revision to improve its content validity for the South African stroke population. This study provides recommendations for the standardization of the tool.
A research report submitted to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy (Neurosciences) February 2016
Keywords: Modified Barthel Index; Stroke